Study on the hydration properties of two polymorphs of Sr4Al6SO16. Issue 10 (15th May 2021) - Ndzila, Jaures Syntyche; Ye, Zhengmao; Jing, Guojian; Lu, Xiaolei; Wu, Jiaming; Zhang, Jinpu; Wang, Shuxian; Cheng, Xin
Abstract: Sr4 Al6 SO16 is a kind of anhydrous sulfoaluminate that belongs to the sodalite family. In this paper, we demonstrate the effect of Fe 3+ ions addition on the hydration properties of two polymorphs of Sr4 Al6 SO16 (namely pure orthorhombic and cubic). In solid-state reaction of orthorhombic Sr4 Al6 SO16, excessive 5 wt% SrSO4 was used to compensate for the loss of sulfur. Results indicate that the hydration rate of cubic phase is faster than that of orthorhombic phase at early stage, but the heat release of the latter is more concentrated. The reason why the cubic phase has a faster earlier hydration kinetics may be due to the incorporation of Fe 3+ ions and the formation of SrFe12 O19 impurity phase, which introduce the defects in the structure, activate the crystal lattice, and increase the hydration activity. Both polymorphs react with water to form the reaction products first, and then no crystalline phase hydration product was precipitated after 72 h. In contrary to the XRD, amorphous AH3 was clearly detected in TGA analysis in hydrated samples, probably due to poor crystallinity which cannot be detected by XRD. In addition, both polymorphs contain a lot of impurity phases, and their amounts are calculated using the Rietveld refinement method. Moreover, the addition of Fe 3+ ions is not only beneficial to adjust the cubic phase content, but also facilitates the relative particle growth. This work provides a useful platform for employing the Fe 3+ ions to regulate the hydration properties of Sr4 Al6 SO16 .